Peran Humas Dalam Membangun Citra Pemerintahan Sumatera Utara Pada Kantor Biro Humas Gubernur - Dolly Indra Syahputra; Yan Hendra; Taufik Wal Hidayat (Universitas Medan Area, 2018)
Thisresearchismotivatedbytheimportance ofpublic relationsroleinbuildingthe imageofgovernment.Thepurposeofthisstudy istoexplaintheroleof publicrelationsin buildingtheimageofthegovernmentofNorthSumatra.Theoriesusedinthisstudyinclude the theoryofcommunication,public relationsandthe theory ofimage. The type ofthis research isqualitative research usingqualitativedecriptive method,Researchdatacollected byinterviewing someresource. Resourcepersonsofthisresearcharepersonnelinpublic relationsdepartmentof North Sumatera such as public relations sub-chairman and four public relations staff, researchresultshowsthatpublicrelationsrole inbuildingimageofNorthSumateraisseen frompublic relationsrole asexpertadvisor,public relationsroleasproblem solver,public relationsrole ascommunicationfacilitator.Overallitcanbeexplainedthatthe public relationsof NorthSumatragovernmenthasdoneitsrolein building theimageofNorth Sumatera government.